Noble metal-free porphyrin covalent organic framework layer for CO2 photoreduction to CO - Hou, Yuxia; Ma, Haizeng; Zhu, Dan; Li, Renlong; Zhao, Ziyan; Chun-Xiang, Li; Cheng-Xing, Cui; Ji-Chao, Wang (Dalton transactions : an international journal of inorganic chemistry, 2024)
The presence of greenhouse CO2 gas in the atmosphere causes serious environmental issues. Consequently, the development of photocatalysts for reducing CO2 is essential for mimicking artificial photosynthesis. In this study, we prepared a 5,15-di(4-aminophenty)-10,20-diphentyporphyrin copper (CuDAPP)–1,3,5-triformylphloroglucinol (TP)–covalent organic framework (COF) layer on a glass sheet via a layer-by-layer (LBL) method. The 2D CuDAPP–TP–COF layer was used as a photocatalyst for CO2 reduction, and it demonstrated excellent photocatalytic activity under gas–solid conditions without sacrificial reagents, noble metals, or photosensitisers. The CO production yield was 282.6 μmol g−1 under visible-light irradiation for 6 h, outperforming the raw material CuDAPP and a mixture of CuDAPP and TP, indicating a high application potential of the 2D porphyrin COF layer material in photocatalytic CO2 reduction.